Pola Seleksi Berdasarkan Minat dan Bakat pada Calon Tenant Wirausaha Fakultas Bioindustri Universitas Trilogi - Maulidian Maulidian; Inanpi Hidayati Sumiasih; Mutiara Dewi Puspitawati; Indri Indrawan (Abdihaz: Jurnal Ilmiah Pengabdian pada Masyarakat, 2019)
Interest-and-Talent-Based Method of Selection in Prospective Entrepreneur at the Faculty of Bioindustry, Trilogi University This program was aimed to determine the selection process based on interests and talents carried out by Bioindustry Entrepreneurship Capacity Development Center (called as PPKWB). This paper can be useful as a reference for conducting the selection process for prospective entrepreneurs in other entrepreneurship development centers. The selection method carried out by PPKWB consisted of 3 stages, namely proposal selection, interview selection, and psychological testing. The result of those activities was 12 selected tenants consisting of groups and individuals as well from 26 tenants registered and participated in the 2019 PPKWB program. The twelve tenants were divided into two, namely individual tenants and group tenants. Group tenants consisted of 2-3 members. The tenants came from several study programs consists of agribusiness, agroecotechnology, and food science and technology study programs. The focus areas of each tenant were food, agriculture, and cosmetics.